Optimizing Communication Skills in Adolescents: Implementing the 'REACH' Method at SMK Husada Amanah, Batu, Indonesia - Dian Pitaloka Priasmoro; Yuni Asri; Melan Noer S; Auliya Hidayat (Kolaborasi: Jurnal Pengabdian Masyarakat, 2023)
Introduction: In the current era of digitalisation, the use of social media has a huge impact on the lives of children and adolescents, one of which is reducing the ability or social communication skills. So teenagers need to be equipped with communication skills. Objective: The purpose of this community service activity is to provide communication training with the 'REACH' method. Method: The methods used in the following community service activities are lectures, training, monitoring and evaluation. The programme was carried out for 2-3 days with a peak on Friday 4 August 2023 which was attended by 64 participants. Result: The results of the service began with social anxiety screening using a questionnaire of 10 questions, it was found that more than half of the respondents 58% experienced moderate social anxiety caused by not being ready to interact socially, and others. Then all participants were given education and all 100% could understand the material, and finally all participants 100% could practice the activities taught Conclusion: In conclusion, Training and education activities need to be provided regularly and continuously to have a long-term effect on individual behaviour change.